2012
DOI: 10.1111/vcp.12012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fixation time using Diff‐Quik for staining of canine mast cell tumor aspirates

Abstract: Alteration in fixation time using Diff-Quik does not improve staining characteristics of mast cell tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
7
1
1
Order By: Relevance
“…20,21 However, this was not confirmed in a recent study. 22 In the present study, an accurate MCT diagnosis could not be made in 5% cases with RS. While this number is not high enough to discourage the use of RS in canine skin tumours cytology, practitioners should be aware that, in a minority of cases, RS may lead to a wrong or inconclusive diagnosis.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…20,21 However, this was not confirmed in a recent study. 22 In the present study, an accurate MCT diagnosis could not be made in 5% cases with RS. While this number is not high enough to discourage the use of RS in canine skin tumours cytology, practitioners should be aware that, in a minority of cases, RS may lead to a wrong or inconclusive diagnosis.…”
Section: Discussioncontrasting
confidence: 66%
“…It was suggested that more prolonged fixation (eg, minutes) would result in a more effective staining . However, this was not confirmed in a recent study …”
Section: Discussionmentioning
confidence: 99%
“…Romanowsky stains have advantages over Papanicolaou stains, including excellent depiction of cytoplasmic detail and superior visibility of bacteria, mucin and colloid, whilst limitations of Romanowsky stains include reduced nuclear and nucleolar detail (Jörundsson et al 1999 ). Mast cell granules are not always easily seen when using Diff-Quik (Jackson et al 2013 ).…”
Section: Stainingmentioning
confidence: 99%
“…At the first inspection before the study initiation, a gingival, ear and dermal swab was done for each cat, rolled over a microscope slide and allowed to dry before staining with Diff-Quik stain (Mercedes Medical, Sarasota, FL, USA) (Jackson et al 2013).…”
Section: Clinical Evaluationmentioning
confidence: 99%